Strategy for Improving Vocational Students' Human Skills through Cross-Level Social Project Mentoring - Prastiantomo, Gregorius Adi; Wijayanto, St Agus; Prasojo, Yohanes Budi; Saputra, Tri Hannanto; Nugroho, Adi (STMIK Widya Cipta Dharma, 2025)
Vocational higher education often emphasizes technical competence (hard skills), whereas modern industrial dynamics demand mastery of human skills such as adaptive communication, empathy, and collaborative leadership. This study aims to analyze the effectiveness of Project-Based Learning (PjBL) implementation in Compulsory Curriculum Courses (MKWK) as a strategy for developing human skills among Politeknik ATMI Surakarta students. Using a descriptive qualitative method, this study involved students in mentoring cross-level social projects at five partner schools in Solo Raya, ranging from elementary to vocational high school levels. Data were collected through participatory observation, in-depth interviews, project portfolio documentation, and Focus Group Discussions. The results indicate that cross-level interaction encourages a significant transformation in students from being technical-minded to becoming more socially aware. Improvements in human skills are concretely visible in adaptive communication skills when teaching elementary students, leadership in managing junior high student group dynamics, and team collaboration in mural projects at vocational schools. This strategy proves effective in bridging the social skill gap of vocational students, preparing them to be graduates who are not only technically competent but also humanist, adaptive, and possess civic engagement.